2021
DOI: 10.1021/acs.jmedchem.1c01254
|View full text |Cite
|
Sign up to set email alerts
|

COUPY Coumarins as Novel Mitochondria-Targeted Photodynamic Therapy Anticancer Agents

Abstract: Photodynamic therapy (PDT) for cancer treatment has drawn increased attention over the last decades. Herein, we introduce a novel family of low-molecular-weight coumarins as potential PDT anticancer tools. Through a systematic study with a library of 15 compounds, we have established a detailed structure–activity relationship rationale, which allowed the selection of three lead compounds exhibiting effective in vitro anticancer activities upon visible-light irradiation in both normoxia and hypoxia (phototherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 50 publications
8
41
0
Order By: Relevance
“…Similarly, Manders’ coefficients were quite high in both compounds ( M 1, M 2 = 0.89 for COUPY 2 ; M 1 = 0.83, M 2 = 0.95 for NC-COUPY-2 ). As previously found with COUPY 2 alone, 31 the mitochondria of HeLa cells after incubation with NC-COUPY-2 showed a characteristic donut-shaped morphology after excitation with the laser beam of the microscope ( Figure S19 ), which point out to the mitochondria stress and could be related with ROS generation upon light irradiation. 42 …”
Section: Results and Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Similarly, Manders’ coefficients were quite high in both compounds ( M 1, M 2 = 0.89 for COUPY 2 ; M 1 = 0.83, M 2 = 0.95 for NC-COUPY-2 ). As previously found with COUPY 2 alone, 31 the mitochondria of HeLa cells after incubation with NC-COUPY-2 showed a characteristic donut-shaped morphology after excitation with the laser beam of the microscope ( Figure S19 ), which point out to the mitochondria stress and could be related with ROS generation upon light irradiation. 42 …”
Section: Results and Discussionsupporting
confidence: 79%
“…The fact that this process was slightly more efficient when the coumarin was encapsulated (Φ Δ = 0.04 for NC-COUPY 2 vs Φ Δ = 0.02 for COUPY 2 ) suggests that nanoencapsulation in a hydrophobic environment has a positive effect on type II PDT photochemical reactions, leading to the generation of singlet oxygen. This conclusion is supported by the fact that the singlet oxygen production for the free coumarin 2 was much more efficient in DCM (Φ Δ = 0.11) 31 than in EtOH/H 2 O 1:1 (v/v) (Φ Δ = 0.02).…”
Section: Results and Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As mentioned above, the poor solubility of DYn-2-Cou can be one reason. Phototoxicity might be another reason for its low labelling ability in living cells, since multiple studies have shown coumarin-containing reagents are toxic under irradiation [31], [32]. We evaluated cell viability with MTT assay.…”
mentioning
confidence: 99%